A Phase I Study of Binimetinib (MEK162) Combined with Pexidartinib (PLX3397) in Patients with Advanced Gastrointestinal Stromal Tumor. (18th June 2019) - Rosenbaum, Evan; Kelly, Ciara; D'Angelo, Sandra P.; Dickson, Mark A.; Gounder, Mrinal; Keohan, Mary L.; Movva, Sujana; Condy, Mercedes; Adamson, Travis; Mcfadyen, Chloe R.; Antonescu, Christina R.; Hwang, Sinchun; et al.
Abstract: Lessons Learned: The combination of pexidartinib and binimetinib was safe and tolerable and demonstrated encouraging signs of efficacy in two patients with advanced gastrointestinal stromal tumor (GIST) refractory to tyrosine kinase inhibitors (TKIs). Molecular profiling of GISTs at diagnosis and upon progression may provide insight into the mechanisms of response or resistance to targeted therapies. Additional trials are needed to further explore combined KIT and MEK inhibition in treatment‐naïve and TKI‐refractory patients with advanced GIST. Background: Nearly all patients with advanced gastrointestinal stromal tumor (GIST) develop resistance to imatinib, and subsequent treatments have limited efficacy. Dual inhibition of KIT and MAPK pathways has synergistic antitumor activity in preclinical GIST models. Methods: This was an investigator‐initiated, phase I, dose escalation study of the MEK inhibitor binimetinib combined with pexidartinib, a potent inhibitor of CSF1R, KIT, and FLT3, in patients with advanced or metastatic GIST who progressed on imatinib. The primary endpoint was phase II dose determination; secondary endpoints included safety, tolerability, and efficacy. An expansion cohort to further evaluate safety and efficacy was planned. Results: Two patients were treated at dose level one (binimetinib 30 mg b.i.d. and pexidartinib 400 mg every morning and 200 mg every evening), after which the study was terminated by the manufacturer. No dose‐limiting toxicities (DLTs) were reported, and treatment was well tolerated. The only grade ≥3 treatment‐emergent adverse event (TEAE) was asymptomatic elevated creatine phosphokinase (CPK). Both patients had a best response of stable disease (SD) by RECIST. Progression‐free survival (PFS) and overall survival (OS) were 6.1 and 14.6 months, respectively, in one patient with five prior lines of therapy. The second patient with NF1 ‐mutant GIST had a 27% decrease in tumor burden by RECIST and remains on study after 19 months of treatment. Conclusion: Pexidartinib combined with binimetinib was tolerable, and meaningful clinical activity was observed in two imatinib‐refractory patients.